SOSYAL MEDYADA VE SİYASAL İLETİŞİMİN ADAY PERSPEKTİFİNDE BASKİL ALGISI - KÜRÜM, ŞEYMA (Fırat Üniveristesi, 2026)
Bu yüksek lisans tezi, sosyal medya ve siyasal iletişimin seçmen algısı üzerindeki etkilerini, yerel siyaset bağlamında Elazığ ili Baskil ilçesi örneği üzerinden incelemektedir. Çalışmanın temel amacı, dijitalleşme süreciyle birlikte dönüşen siyasal iletişim pratiklerinin, küçük yerleşim yerlerinde seçmen davranışı, siyasal katılım ve aday algısı üzerindeki rolünü ortaya koymaktır. Tezin kuramsal çerçevesi; siyasal iletişim, kitle iletişimi, yeni medya, sosyal medya, seçmen davranışı, propaganda, dijital siyaset ve beden dili literatürüne dayanmaktadır. Bu kapsamda literatür taraması bölümünde siyasal iletişimin tarihsel gelişimi, geleneksel ve dijital medya arasındaki ayrım, sosyal medyanın siyasal katılıma etkileri, seçmen algısının oluşum süreçleri ve yerel siyasal iletişim stratejileri ayrıntılı biçimde ele alınmıştır. Ayrıca Barack Obama'nın örnek seçim kampanyası, Baskil yerel seçimleriyle karşılaştırmalı olarak değerlendirilmiştir. Araştırma, nitel araştırma yöntemi çerçevesinde tasarlanmış olup, veri toplama sürecinde yarı yapılandırılmış görüşme tekniği kullanılmıştır. Çalışmanın saha boyutu, Elazığ ili Baskil ilçesinde 2024 yerel seçim sürecinde aday adayı olan üç katılımcı ile gerçekleştirilen görüşmelerle sınırlandırılmıştır. Örneklemin üç aday adayı ile sınırlı tutulmasının temel nedeni; çalışmanın nicel genelleme amacı taşımaması, yerel siyaset bağlamında derinlemesine ve bağlamsal veri elde etmeyi hedeflemesi ve nitel araştırma yaklaşımının gerektirdiği ayrıntılı analiz sürecidir. Bu doğrultuda araştırmada anket, ölçek veya istatistiksel genelleme yöntemleri kullanılmamış; elde edilen veriler betimsel ve tematik analiz yöntemiyle çözümlenmiştir. Bulgular, Baskil ilçesi özelinde siyasal iletişim pratiklerinin ve sosyal medya kullanım biçimlerinin anlaşılmasına yönelik yorumlayıcı bir çerçeve sunmaktadır. Bulgular bölümünde; katılımcıların adaylık motivasyonları, sosyal medya kullanım alışkanlıkları, dijital ve geleneksel medya algıları, seçmenle kurulan iletişim biçimleri ve kampanya stratejileri analiz edilmiştir. Elde edilen bulgular, Baskil gibi küçük ve yüz yüze iletişimin güçlü olduğu yerleşimlerde, sosyal medyanın tek başına belirleyici bir unsur olmadığını; ancak siyasal farkındalık yaratma, görünürlük sağlama ve gündem oluşturma açısından tamamlayıcı ve destekleyici bir araç olarak önemli bir işlev üstlendiğini göstermektedir. Araştırma sonuçları, yerel siyasette ev ziyaretleri, aday ziyaretleri, salon toplantıları ve açık hava toplantılarının hâlen etkili olduğunu; buna karşın sosyal medyanın aday imajı, söylem bütünlüğü ve seçmenle sürekli temas açısından stratejik bir rol oynadığını ortaya koymaktadır. Ayrıca beden dili ve sözsüz iletişimin, seçmen algısı üzerinde güçlü ve belirleyici bir etkiye sahip olduğu tespit edilmiştir. Sonuç ve tartışma bölümünde elde edilen bulgular literatürle karşılaştırılmış; yerel siyasal iletişim çalışmalarına yönelik teorik ve pratik çıkarımlar sunulmuş ve gelecekte yapılacak araştırmalar için öneriler geliştirilmiştir. Çalışma, yerel siyaset–sosyal medya ilişkisini mikro ölçekte, saha temelli ve nitel bir yaklaşımla ele alması bakımından özgün bir nitelik taşımaktadır.

This master's thesis examines the effects of social media and political communication on voter perception through the example of Baskil district of Elazığ province in the context of local politics.his master's thesis examines the effects of social media and political communication on voter perception through the example of Baskil district of Elazığ province in the context of local politics. The main purpose of the study is to reveal his master's thesis examines the effects of social media and political communication on voter perception through the example of Baskil district of Elazığ province in the context of local politics. The main purpose of the study is to reveal the role of political communication practices, which have been transformed with the digitalization process, on voter behavior, political participation and candidate perception in small settlements. The theoretical framework of the thesis is based on the literature on political communication, mass communication, new media, social media, voter behavior, propaganda, digital politics and body language. In this context, the historical development of political communication, the Decoupling between traditional and digital media, the effects of social media on political participation, the formation processes of voter perception and local political communication strategies are discussed in detail in the literature review section.n this context, the historical development of political communication, the Decoupling between traditional and digital media, the effects of social media on political participation, the formation processes of voter perception and local political communication strategies are discussed in detail in the literature review section. In addition, Barack Obama's exemplary election campaign was evaluated in comparison with the Basque local elections. The research was designed within the framework of qualitative research method and semi-structured interview technique was used in the data collection process. The field dimension of the study is limited to the interviews conducted with three participants who were candidates in the 2024 local elections in Baskil district of Elazığ province.ield dimension of the study is to the interviews conducted with three participants who were candidates in the 2024 local elections in Baskil district of Elazığ province. The main reason why the sample was limited to three candidate candidates is that the study does not aim to make quantitatfield dimension of the study is limited to the interviews conducted with three participants who were candidates in the 2024 local elections in Baskil district of Elazığ province. The main reason why the sample was limited to three candidate candidates is that the study does not aim to make quantitative generalizations, but aims to obtain in-depth and contextual data in the context of local politics and the detailed analysis process required by the qualitative research approach. In this regard, no survey, scale or statistical generalization methods were used in the research; the data obtained were analyzed using descriptive and thematic analysis methods. The findings provide an interpretive framework for understanding political communication practices and social media usage patterns in the Baskil district.he findings provide an interpretive framework for understanding political communication practices and social media usage patterns in the Baskil district. In the Results section, the participants' motivations for candidacy, social media usage habits, digital and traditional media perceptions, forms of communication established with the voter and campaign strategies were analyzed. The findings obtained indicate that in small settlements such as Baskil, where face-to-face communication is strong, social media alone is not a determining factor; However, it shows that it plays an important function as a complementary and supportive tool in terms of raising political awareness, providing visibility and creating an agenda.owever, it shows that it plays an important function as a complementary and supportive tool in terms of raising political awareness, providing visibility and creating an agenda. Research results reveal that home visits, candidate visits, hall meetings and open airver, it shows that it plays an important function as a complementary and supportive tool in terms of raising political awareness, providing visibility and creating an agenda. Research results reveal that home visits, candidate visits, hall meetings and open air meetings are still effective in local politics; however, social media plays a strategic role in terms of candidate image, discourse integrity and continuous contact with voters. It has also been determined that body language and nonverbal communication have a strong and decisive effect on voter perception. In the results and discussion section, the findings were compared with the literature; theoretical and practical implications for local political communication studies were presented and suggestions for future research were developed.n the results and discussion section, the findings were compared with the literature; theoretical and practical implications for local political com
The perception of Baskil in social media and political communication from the candidate's perspective
12.09.2026 tarihine kadar kullanımı yazar tarafından kısıtlanmıştır.
Keywords: Gazetecilik